Identifying, creating, and testing urban planning measures for transport walking: Findings from the Australian national liveability study. (June 2017) - Badland, Hannah; Mavoa, Suzanne; Boulangé, Claire; Eagleson, Serryn; Gunn, Lucy; Stewart, Joshua; David, Stephanie; Giles-Corti, Billie
Abstract: A vast body of research demonstrates that living in ׳more walkable׳ neighbourhoods is associated with increased walking, and in turn, positively impacts selected health behaviours and outcomes. Yet, walkable neighbourhoods are not always delivered. The aims of this study were to identify Australian urban planning policies designed to foster ׳walkability׳, and to test measures based on these policies with transport walking behaviours in adults. Overall, 14 Australian state level urban planning policies related to walking were identified. Spatial measures were developed based on these urban planning policies, and linked with geocoded population survey data. Associations between the urban planning spatial measures and neighbourhood transport walking behaviours were tested in a sample of urban adults ( n =16, 890). The odds of transport walking were significantly higher for those living in ׳more walkable׳ (compared with less walkable) neighbourhoods; i.e. with more connected street networks, higher residential densities, more destinations available, and shorter block sizes and distances to activity centres. Our findings showed that all 14 policies implemented in GIS were independently associated with walking in the residential neighbourhood. The associations observed tended to be stronger than previously shown, especially in regard to the dwelling density and daily destination measures. Our findings support the calls for more research using policy-relevant measures in order to better inform urban planning guidance, and suggests that if current spatially derived urban policies were implemented, it may increase transport walking. This research has the potential to contribute to building consensus for urban planning policies related to walking. Highlights: 14 Australian state-level urban planning policies related to walking were identified and implemented in GIS. All 14 policies implemented in GIS were independently associated with walking in the residential neighbourhood. Associations observed were stronger than previously shown, largely because of specificity.